Evaluation of Open Access Websites for Anesthesia Education. (18th August 2022) - Evans, Faye M.; Krotinger, Anna A.; Lilaonitkul, Maytinee; Khaled, Hiba F.; Pereira, Gretchen A.; Staffa, Steven J.; Wolbrink, Traci A.
Abstract : BACKGROUND: While the prevalence of free, open access medical education resources for health professionals has expanded over the past 10 years, many educational resources for health care professionals are not publicly available or require fees for access. This lack of open access creates global inequities in the availability and sharing of information and may have the most significant impact on health care providers with the greatest need. The extent of open access online educational websites aimed for clinicians and trainees in anesthesiology worldwide is unknown. In this study, we aimed to identify and evaluate the quality of websites designed to provide open access educational resources for anesthesia trainees and clinicians. METHODS: A PubMed search of articles published between 2009 and 2020, and a Startpage search engine web search was conducted in May 2021 to identify websites using the following inclusion criteria: (1) contain educational content relevant for anesthesia providers or trainees, (2) offer content free of charge, and (3) are written in the English language. Websites were each scored by 2 independent reviewers using a website quality evaluation tool with previous validity evidence that was modified for anesthesia (the Anesthesia Medical Education Website Quality Evaluation Tool). RESULTS: Seventy-five articles and 175 websites were identified; 37 websites met inclusion criteria. The most common types of educational content contained in the websites included videos (66%, 25/37), text-based resources (51%, 19/37), podcasts (35%, 13/37), and interactive learning resources (32%, 12/37). Few websites described an editorial review process (24%, 9/37) or included opportunities for active engagement or interaction by learners (30%, 11/37). Scores by tertile differed significantly across multiple domains, including disclosure of author/webmaster/website institution; description of an editorial review process; relevancy to residents, fellows, and faculty; comprehensiveness; accuracy; disclosure of content creation or revision; ease of access to information; interactivity; clear and professional presentation of information; and links to external information. CONCLUSIONS: We found 37 open access websites for anesthesia education available on the Internet. Many of these websites may serve as a valuable resource for anesthesia clinicians looking for self-directed learning resources and for educators seeking to curate resources into thoughtfully integrated learning experiences. Ongoing efforts are needed to expand the number and improve the existing open access websites, especially with interactivity, to support the education and training of anesthesia providers in even the most resource-limited areas of the world. Our findings may provide recommendations for those educators and organizations seeking to fill this needed gap to create new high-quality educational websites.